Categorizing Languages and Speakers: Processes of Erasure in Data Treatment and Presentation - Busch, Brigitta (Diversité urbaine)

(untitled) (Chaire BMO en diversité et gouvernance, 2020)
This article examines how census data are processed by statistical offices. It first investigates how the language categories displayed in language statistics are actually elaborated. It then considers the mechanisms by which speakers are assigned to specific language categories. It addresses the language ideologies underlying both these processes and the ways in which a certain view of the world is thus reproduced and reinforced. Finally, it discusses how these practices are linked with the paradigms of statehood and territoriality, and how they have been developed historically in the contexts of colonization and of ethno-national conflict. The paper draws on censuses and statistics in Austria to explore these questions, but the procedures used correspond to those in other countries that follow the guidelines set by the Conference of European Statisticians (2015).